Investigation of wear characteristics of spark plasma sintered W-25wt%Re alloy and W-25wt%Re-3.2wt%HfC composite. (December 2017) - Iqbal, Zafar; Merah, Nesar; Nouari, Saheb; Shuaib, Abdel Rahman; Al-Aqeeli, Nasser
Abstract: Wear characteristics of monolithic W-25wt%Re alloy spark plasma sintered at 1500 °C, 1700 °C and 1800 °C and W-25wt%Re-3.2wt%HfC composite sintered at 1800 °C, have been investigated. Higher sintering temperature of W-Re alloys resulted in higher relative density, microhardness and thermal conductivity and consequently better tribological characteristics. Wear resistance was improved with the addition of 3.2wt% HfC to W-25wt%Re matrix. SEM analyses revealed that the dominant wear mechanism in monolithic alloys was abrasive in nature while that in the composite was mostly adhesive with the presence of HfC debris and pullout sites. The coefficient of friction (COF) of the monolithic W-25wt%Re alloy increased with increasing sintering temperature. W-25wt%Re-3.2wt%HfC composite showed lower average COF and specific wear rate than those of its monolithic counterpart. Highlights: A comparative wear behavior study of SPSed W-Re alloy and W-Re-HfC composite is reported. Addition of HfC improves the wear resistance and Coefficient of Friction for the composite. Developed wear resistant tool materials have potential application for friction stir welding of steel.